Pemanfaatan E-Commerce pada Industri Kreatif di Kecamatan Margahayu Kabupaten Bandung - Ranti Hajrianti; Enok Maryani; Bagja Waluya (Manajemen dan Pariwisata, 2023)
The creative industry in Margahayu District, Bandung Regency has very high potential. However, during the Covid-19 pandemic, the demand for products in this creative industry actually decreased. This decline phenomenon can weaken production activities, and can even threaten the existence of creative industries in Margahayu District. Therefore, creative industry players in Margahayu District need to determine the right survival strategy in order to maintain their existence. One effort that can be implemented to overcome these problems is to utilize e-commerce. This study aims to evaluate utilization e-commerce as a product marketing media and analyze the constraints faced in utilization e-commerce in the creative industries in Margahayu District, Bandung Regency. The method used in this study is a descriptive method with a quantitative approach, and applies survey methods in its implementation. The data analysis technique used in this study is through percentage calculations. The results of this study indicate that the creative industries in Margahayu Sub-District have utilized them e-commerce as a product marketing medium well because it is supported by the availability of the internet, the ease of information, and the availability of human resources. Meanwhile, the obstacles faced in the utilization of creative industries in Margahayu District, Bandung Regency consist of unstable internet access, platform e-commerce which often experience interruptions, as well as limited time to serve consumers directly.